Clashing Clocks: Temporal interactions among the mara, European hare, and Pampas fox in agricultural Patagonia (Semiárida, 2025)
This study examines the overlap of daily activity patterns (DAPs) among three mammal species in agro-pastoral landscapes of northeastern Patagonia: the mara (Dolichotis patagonum), an endemic Argentine species; the European hare (Lepus europaeus), an invasive exotic species; and the Pampas fox (Lycalopex gymnocercus), a native predator. Using camera traps and DAP analyses, we identified marked differences in activity schedules among the species. The mara exhibited a strictly diurnal pattern, the hare was exclusively nocturnal, and the fox was mainly nocturnal with some crepuscular activity. The temporal segregation found between the mara and the other two species, and the temporal overlap between the pampas fox and the European hare, suggest possible ecological interactions such as low competition between the mara and the hare, and a higher predation risk for the hare by the Pampas fox. However, the existence of competition and predation ultimately depends on multiple factors that should be addressed in detail in future studies. These results provide valuable insights into the strategies of these species in landscapes transformed by human use, a context that remains scarcely studied in northeastern Patagonia.
Keywords: Monte; daily activity patterns; temporal overlap; temporal segregation